2006
DOI: 10.1002/ejic.200500880
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of the Ordered Double Perovskite Sr2MnTeO6

Abstract: The ordered double perovskite Sr 2 MnTeO 6 was prepared by the freeze-drying method. The nuclear and magnetic structures were determined by both X-ray and neutron (D2B and D1B) powder diffraction. A distorted, double perovskite structure type described by the monoclinic P12 1 /n1 space group is observed at room temperature and down to 4 K. The room temperature EPR spectrum shows an isotropic signal centered at a g value of 1.998 indicating that manganese ions are in the +2 oxidation state. At low temperature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…It is also worth noting that the Weiss constant values are all high and negative, θ=−336 and −417 K, in both ranges of temperature, which can be related to AFM interactions. Such a response appears to be expected in a perovskite only containing Mn 4+ as paramagnetic cations, as has been observed in similar systems 30,32 . However, other authors have reported 24 previously that FM interactions are operative in SMTO.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…It is also worth noting that the Weiss constant values are all high and negative, θ=−336 and −417 K, in both ranges of temperature, which can be related to AFM interactions. Such a response appears to be expected in a perovskite only containing Mn 4+ as paramagnetic cations, as has been observed in similar systems 30,32 . However, other authors have reported 24 previously that FM interactions are operative in SMTO.…”
Section: Resultssupporting
confidence: 74%
“…This is not surprising considering the oxidation states and sizes of cations located at the B-sublattice (almost only Mn 41 and Ti 41 ), in contrast to the case of wellknown double perovskites. [28][29][30] Another interesting result obtained by this technique is the stabilization of surprisingly small crystals (considering the thermal treatment used), clearly below 50 nm in all cases, as shown in Fig. 5 as an example.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Under these conditions only nnn and tnn interactions are possible and for this kind of materials antiferromagnetic transitions are observed below 30 K: Sr 2 MnTeO 6 [37], LaSrMnNbO 6 [38], La 2 CoTiO 6 and La 2 NiTiO 6 [39], LaBaTaNiO 6 and LaBaTaCoO 6 [40], LaPbM SbO 6 where M¼Mn, Co and Ni [41], among others.…”
Section: Tablementioning
confidence: 96%
“…As a result, as the Mn(III)/Mn(IV) ratio becomes larger, the peak to peak linewidth ΔH pp value also increases. 21 . Figure 7 shows the thermal evolution of χ m T of all the samples.…”
Section: Characterizationmentioning
confidence: 99%